Determination of Phenolic and Flavonoid Contents, Antioxidant Activities and GC-MS Analysis of Clinacanthus nutans (Acanthaceae) in Different Locations - Noor Zafirah Ismail; Hasni Arsad; Mohammed Razip Samian; Mohammad Razak Hamdan (AGRIVITA, Journal of Agricultural Science, 2017)
Clinacanthus nutans is an essential medicinal plant that had been used in various local remedies to treat many illnesses. A study had been conducted to determine the phenolic, flavonoid, antioxidant activities and phytochemical compounds of C. nutans in different locations. C. nutans were harvested from eight locations and the leaves were extracted with 80 % methanol by maceration process. Then, the phytochemical screening using Gas Chromatography-Mass Spectrometry (GC-MS), 2,2 diphenyl-2-picrylhydrazyl hydrate (DPPH) assay method, total phenolic content by Folin Ciocalteu’s assay method and total flavonoid content by aluminium chloride (AlCl3) were carried out. The C. nutans extracts showed higher antioxidant activities than phenolic and flavonoid content. The neutral pH sandy clay soil from location KKK (Kuala Ketil, Kedah, Malaysia) had higher antioxidant activities (58.0 %), phenolic (44.1 mg GA.100 g-1) and flavonoid content (30.8 mg QE.100 g-1) compared to other locations. The GC-MS analysis showed the presence of phytochemicals constituents of 20 compounds. The results revealed that environmental factors (light intensity, temperature and soil characteristics) of eight locations were responsible for variations of phenolic, flavonoids, antioxidants and GC-MS analysis in C. nutans. The findings of this study will provide baseline data for future breeding programs for commercial cultivation.